Efficacy of intermittent peritoneal dialysis in renal causes of acute kidney injury in children - Huq, Mashhura; Afroz, Shireen; Akter, Sabrina; Newaz, Moshrefa; Nasrin, Tahera; Hossain, Fahmida (International Journal of Contemporary Pediatrics, 2024)
Background: In low-resource settings like Bangladesh, intermittent peritoneal dialysis (IPD) has been identified as the preferred modality for the management of AKI. PD is a safe, simple and inexpensive procedure and has been used in pediatric AKI patients. However, its effectiveness in treatment of renal AKI warrants further exploration. To evaluate the efficacy of IPD in treating pediatric renal AKI patients. Method: This prospective and interventional study conducted in the Department of Paediatric Nephrology at Bangladesh Shishu Hospital and Institute from January 2020 to December 2021. Children aged 1 month to 12 years of either sexes with renal AKI stages 2 or 3 who required PD were included. Each patient had IPD for 72 hours. Every day, the clinical and laboratory markers were measured; on the third day, or 72 hours later, the results were compared. Results: Majority of patients were from 1-5 years age group and predominantly male. Following 3 days of IPD, clinical parameters (tachycardia, tachypnea and edema) improved significantly. Oedema found in 23 patients before PD, however, 5 patients got a relief from it (p=0.016) after PD. The urea reduction ratio in renal AKI patients increased from 19.3 to 40.7 ml/kg/hr days, with urinary output increasing from 0.02 to 0.50 ml/kg/hr at day 3 (p<0.001). After PD, there was a significant decrease in creatinine, urea, and potassium levels (p<0.001). Besides, a noteworthy improvement of 40.7%, 36.5% and 47.7% were observed in creatinine, urea and bicarbonate levels respectively. Conclusion: IPD is well-effective in treating renal AKI in children by observing a greater improvement in clinical and laboratory parameters in the patients.